Effort Increase Learning Outcomes on Subject Poetry People Eye Lesson Language Indonesia Student Through Media Videos Learning - Fhadira Insani Putri; Wazha Bickie Maundeni (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to investigate the impact of using multimedia learning on students’ academic performance. Specifically, it examines efforts to enhance learning outcomes in the discussion of folk poetry in Indonesian language subjects for seventh-grade students through the use of educational videos. Methodology: This study employs a CAR approach, allowing for continuous evaluation and improvement of the learning process. The research was conducted at Junior high school Jambi. The subjects were 32 seventh-grade students, consisting of 16 males and 16 females. Data collection techniques included observation, data recording, document analysis, questionnaires, tests, and documentation. The data were analyzed using critical analytical techniques. Main Findings: The results from the first cycle of the CAR indicated an improvement in students’ abilities compared to the pre-action phase, as evidenced by increased learning outcomes in the discussion of folk poetry in Indonesian language lessons. The percentage of students achieving the Minimum Competency Criteria was 46.9% in the first cycle, which significantly increased to 84.38% in the second cycle. Novelty/Originality of this study: The development of multimedia technology offers significant opportunities to transform student learning. Multimedia tools also enable teachers to develop effective teaching techniques, leading to optimal and maximum learning outcomes. The success of teachers in enhancing students’ potential is a primary goal in education, aiming to achieve high student performance and desired learning outcomes. Generally, two factors influence learning outcomes: internal and external factors. These factors interact in the individual student’s learning process, determining the quality of learning outcomes.